2022
DOI: 10.3390/economies10040077
|View full text |Cite
|
Sign up to set email alerts
|

FDI and Institutions in BRIC and CIVETS Countries: An Empirical Investigation

Abstract: In recent years, a number of countries with emerging economies have proceeded to use market-oriented strategies, deregulation and reforms in order to attract more foreign investors and attract foreign direct investment (FDI) inflows. The present paper aims to empirically investigate the role of governance in attracting FDI using panel data and comparing two groups of fast-growing emerging countries, namely BRIC (Brazil, Russia, India, China) and CIVETS (Colombia, Indonesia, Vietnam, Egypt, Turkey and South Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 126 publications
1
9
0
Order By: Relevance
“…Çinar (2017) specifically showed that the adverse impact of terrorism is more pronounced in less developed countries. Furthermore, studies conducted by Ali et al (2017) for Pakistan, Bezic et al (2016) for European countries, Filer and Stanišić (2016) for a world sample of 160 countries, Kinyanjui (2014) for Kenya, Iheonu and Ichoku (2022) for African economies, Kechagia and Metaxas (2017) for Asian economies support the notion that terrorist activities negatively affect foreign direct investment inflow. Nabin et al (2022) confirmed the negative impact of terrorist activities on economic development in 151 countries, both developing and developed, between 2005 and 2019.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Çinar (2017) specifically showed that the adverse impact of terrorism is more pronounced in less developed countries. Furthermore, studies conducted by Ali et al (2017) for Pakistan, Bezic et al (2016) for European countries, Filer and Stanišić (2016) for a world sample of 160 countries, Kinyanjui (2014) for Kenya, Iheonu and Ichoku (2022) for African economies, Kechagia and Metaxas (2017) for Asian economies support the notion that terrorist activities negatively affect foreign direct investment inflow. Nabin et al (2022) confirmed the negative impact of terrorist activities on economic development in 151 countries, both developing and developed, between 2005 and 2019.…”
Section: Literature Reviewmentioning
confidence: 88%
“… Western Balkan countries [ 49 ] 2000–2017; Meta analysis Institutional quality has a positive impact on FDI inflows. BRICS [ 50 ] 2002–2019; Panel Regression Rule of law, regulatory quality, political stability and absence of violence have a positive impact on FDI inflows in BRIC. BRIC and CIVETS Control of corruption, government effectiveness, regulatory quality, political stability and absence of violence have a positive impact on FDI inflows in CIVETS.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Market size can be measured through the GDP growth rate of a country [ 50 ]. The macroeconomic stability is measured through a set of variables such as financial development, total capital formation [ 43 ], international trade [ 57 ], exchange rate [ 58 , 59 ] and inflation [ 60 , 61 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies have also shown that terrorist activities impact negatively on foreign direct investment inflow ( e.g . Kinyanjui, 2014, for Kenya; Bezic et al, 2016, for European countries; Ali et al, 2017, for Pakistan; Filer & Stanisic, 2016, for a world sample of 160 countries; Kechagia & Metaxas, 2017, for Asian economies; Iheonu & Ichoku, 2022, for African economies). In addition, Mehmood and Mehmood (2016) and Siddique et al (2017) also found that terrorism deters domestic investment.…”
Section: An Overview Of the Literaturementioning
confidence: 99%